The Bosnian Army During the Time of Ban Matej Ninoslav - Zilić, Adis (Historical Thought, 2025)
The aim of the paper is to examine the political circumstances in Bosnia and the military capacity of the country during the fourth and fifth decades of the thirteenth century, under the rule of Ban Matej Ninoslav. This period was characterized by a turbulent phase of transition for the Bosnian state, whose structure reflected the features typical of the High Middle Ages. Foreign political actors – primarily the Kingdom of Hungary and the Papacy – became actively involved as interested parties, focusing their attention on Bosnia’s political and religious conditions. The defining characteristic of this two-decade span was Hungary’s persistent threat of military intervention under the pretext of crusading campaigns, which eventually culminated in actual military expeditions. The Bosnian army emerged and evolved amid circumstances marked by warfare and violence. Given the limited preservation of primary sources, this study seeks, through indirect evidence, to identify the fundamental social characteristics of the Bosnian state and to assess its military strength within the specified historical framework.